Perceptions of developers in green home project in Kuala Lumpur - Alsaeedi, Yaser Abdulwahab Ali (2019)
Green home is rapidly becoming a strong momentum in the construction industry after recognizing many negative environmental issues & problems and potential social and economical benefits around the world. However, developers still using conventional way to construct the housing. This gives huge impact to the environment and also human health. Meanwhile, there are actually some barriers hinder developers to adopt this in their projects. This study examines the perceptions of the developers in Kuala Lumpur on the future of the green housing sector for the next 20 years, their commitment about green housing and propose solution for improvement green home project in Kuala Lumpur. The methodology used in this study is questionnaire and it is targeted 200 developer’s firms in Kuala Lumpur.The introduction of Green home rating system, improvement of awareness and knowledge among the stakeholders, support from the government and local industry and the effect of competitive advantage would support brighter future. Meanwhile, the status quo in rules and regulation, lack of public interest and demand, organization disinterest, local authority enforcement and project cost escalation would hinder a faster progress. Finally, this study could really help the awareness on environment and in improve the green home project among developers.